Vietnamese EFL Pre-service Teachers’ Perceptions of Attainments (Achievements) and Difficulties from a Teaching Practicum - Tran, Hue Thanh Thi; Bui, Trang Diem Le; Ly, Trang Minh Thi (Vietnam Journal of Education, 2023)
This study explored how a teaching practicum prepared pre-service English teachers (PSETs) for their profession and what difficulties they encountered during their practicum. Forty-seven PSETs of the 2019 intake at a Vietnamese university provided information via a questionnaire, and eight participated in follow-up interviews. The PSETs’ perceived gains in teaching competencies were examined with reference to Vietnam’s English Teacher Competency Framework (ETCF), issued in 2012 by the Ministry of Education and Training (MOET). The results indicated that the teaching practicum significantly aided the PSETs’ attainments of most competency domains in the ETCF, particularly those that are associated with a greater appreciation of the values and responsibilities of being a teacher, enhanced knowledge of the curriculum and the English language, as well as the ability to reflect on and improve teaching practices. However, certain competency indicators across the competency domains, including practice with assessment, handling difficult pedagogical incidents, and organizing extracurricular activities to create a supportive and meaningful learning environment, were less clearly obtained than the others. Dealing with time constraints and workload, insufficient preparation for classroom practice, and safety precautions to deal with the post-COVID-19 pandemic were some of the major obstacles the PSETs encountered. The results have important implications for pre-service teacher education programs and the implementation of the ETCF for teacher development.